Inquiry-based learning through lesson study to improve the students’ mathematical problem-solving ability - Z Mujtahid; F Athar; D Pratama (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
Today, one of the skill that student needed to be success in mathematics is problem solving ability. As educators we are charged with the great challenge and responsibility of engaging students in learning so that they develop the skills and knowledge they need to functionin today’s world. Inquiry-based learning is an approach to teaching and learning that places students’ questions, ideas and observations at the centre of the learning experience. Lesson study(jugyō kenkyū) is an inquiry model of teacher professional development used extensively throughout Japan and has begun to capture the attention of the American educational communityas a potential strategy for enhancing teacher professional development in America. There wouldbe implemented inquiry-based learning through lesson study about composition function and inverse function to improve the students’ mathematical problem-solving ability and used testsand questioners to know the students’ improvement. In this research, there was an improvement of students’ mathematical problem-solving ability after implemented these methods. So, wecould know that inquiry-based learning through lesson study were successful to improve thestudents’ mathematical problem-solving ability.1. Introduction Problem solving is an integral part of all mathematics learning, and so it should not be a